A cryptic rock‐paper‐scissors game between Drosophila males. Issue 5 (25th February 2013) - Chippindale, Adam K.
<x xml:space="preserve">Abstract</x> Explaining the maintenance of genetic variation in characters associated with Darwinian fitness is a preoccupation of evolutionary biologists. Spatial or temporal variation in the environment can certainly promote polymorphism, yet even populations of 'model organisms', like fruit flies, kept on invariant protocols for hundreds of generations in the laboratory often show fitness variation that exceeds what would be expected from the input of new mutations alone. Such observations suggest either complexities of selection or of genetic architecture, and offer a powerful tool for the study of mechanisms that promote stable polymorphism. In this issue of Molecular Ecology, Zhang et al. (2013) report examples of nontransitivity in the outcome of postcopulatory sexual selection in the fruit fly, Drosophila, that follow the rules of the popular stalemate‐breaking game roshambo – or rock, paper, scissors (RPS). The important feature of RPS is that while each strategy beats one other, it in turn is beaten by the third. Using chromosome extraction lines, the authors confirm earlier findings that the outcome of postcopulatory sexual selection via sperm competition for a male depends, in part, upon the competitor male's genotype. But taking it one step further, they demonstrate the nontransitivities between males required for circular RPS cycles in sperm competition between males, and are able to identify at least four associated loci. Because the postmating phenotype involves hundreds of potentially interacting peptides and receptors, this is an important step to understanding the persistence of variation in a critical component of male fitness.